2012
DOI: 10.1084/jem.20111504
|View full text |Cite
|
Sign up to set email alerts
|

B and T cells collaborate in antiviral responses via IL-6, IL-21, and transcriptional activator and coactivator, Oct2 and OBF-1

Abstract: Transcriptional activator Oct2 and cofactor OBF-1 regulate B cell IL-6 to induce T cell production of IL-21, to support Tfh cell development in antiviral immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
198
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(221 citation statements)
references
References 91 publications
(193 reference statements)
13
198
2
1
Order By: Relevance
“…In contrast, these organs were repopulated by comparable numbers of Pou2af1 −/− and Pou2af1 +/+ CD4 + T cells (Fig 4A). In line with the recent observation that the development of GC B cells is hampered in Pou2af1 −/− mice (Karnowski et al , 2012), we observed a significant reduction in the frequency and numbers of FAS + GL7 + GC B cells within the population of Pou2af1 −/− B cells in the BM chimeras upon immunization with SRBCs (Figs 4B and EV1A). The most striking observation was, however, a defect in the development of Tfh cells from mature, recirculating Pou2af1 −/− CD4 + T cells in these experiments.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In contrast, these organs were repopulated by comparable numbers of Pou2af1 −/− and Pou2af1 +/+ CD4 + T cells (Fig 4A). In line with the recent observation that the development of GC B cells is hampered in Pou2af1 −/− mice (Karnowski et al , 2012), we observed a significant reduction in the frequency and numbers of FAS + GL7 + GC B cells within the population of Pou2af1 −/− B cells in the BM chimeras upon immunization with SRBCs (Figs 4B and EV1A). The most striking observation was, however, a defect in the development of Tfh cells from mature, recirculating Pou2af1 −/− CD4 + T cells in these experiments.…”
Section: Resultssupporting
confidence: 92%
“…Along this line, Karnowski et al (2012) have recently reported that Pou2af1 −/− CD4 + T cells are not impaired in their ability to differentiate into Tfh cells during influenza infection in mice reconstituted with wild‐type B cells. Viral infections, however, elicit strong Toll‐like receptor signals not only in DCs and B cells, but also in CD4 + T cells that, depending on the pathogenic stimulus and the anatomic compartment, promote the generation of Tfh cells and adaptive immune responses (Hou et al , 2011; Rookhuizen & Defranco, 2014; Kubinak et al , 2015).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Littermate and DM2 mice were infected with influenza A virus and DTX was administered on days 7-9 of infection (Fig. 5A) during the expansion and differentiation of CD8 + T cells, GC B cells, and Tfh cells (27,28). The medLNs, lung, and spleen were analyzed on day 10 for the CD8 + T-cell responses; the Tfh, and B-cell responses were measured in the medLNs only.…”
Section: Ln Frcsmentioning
confidence: 99%